Petroleum hydrocarbon and microbial community structure successions in marine oil-related aggregates associated with diatoms relevant for Arctic conditions. (October 2018) - Netzer, Roman; Henry, Ingrid A.; Ribicic, Deni; Wibberg, Daniel; Brönner, Ute; Brakstad, Odd G.
Abstract: Oil-related aggregates (ORAs) may contribute to the fate of oil spilled offshore. However, our understanding about the impact of diatoms and associated bacteria involved in the formation of ORAs and the fate of oil compounds in these aggregates is still limited. We investigated these processes in microcosm experiments with defined oil dispersions in seawater at 5 °C, employing the Arctic diatom Fragilariopsis cylindrus and its associated bacterial assemblage to promote ORA formation. Accumulation of oil compounds, as well as biodegradation of naphthalenes in ORAs and corresponding water phases, was enhanced in the presence of diatoms. Interestingly, the genus Nonlabens was predominating the bacterial communities in diatom-supplemented microcosms, while this genus was not abundant in other samples. This work elucidates the relevance of diatom biomass for the formation of ORAs, microbial community structures and biodegradation processes in chemically dispersed oil at low temperatures relevant for Arctic conditions. Highlights: n-Alkane depletion from the water phases caused by accumulation and biodegradation processes. Diatoms stimulated aggregation accompanied by increased accumulation of hydrocarbons. Microbial communities in aggregates are dominated by diatom-associated bacteria. Possible hydrocarbon degradation by the diatom associated genus Nonlabens . Aromatic hydrocarbon degrader Sphingomonadaceae became abundant in oil samples without diatoms.